2018
DOI: 10.20944/preprints201811.0460.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prediction of Confusion Attempting Algebra Homework in an Intelligent Tutoring System through Machine Learning Techniques for Educational Sustainable Development

Abstract: Incorporating substantial sustainable development issues into teaching and learning is the ultimate task of Education for Sustainable Development (ESD). The purpose of our study is to identify the confused students who have failed to master the skill(s) given by the tutors as a homework using Intelligent Tutoring System (ITS). We have focused ASSISTments, an ITS in this study and scrutinized the skill-builder data using machine learning techniques and methods. We used seven candidate models that include: Na&am… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Here, we can see that all independent variables are significant predictors based on their P-values [62], as shown in Table 4. For statistical analysis, we used the statistical programming language R [63] and used RStudio [64] to perform basic descriptive and regression analysis.…”
Section: ) Statistical Analysismentioning
confidence: 72%
“…Here, we can see that all independent variables are significant predictors based on their P-values [62], as shown in Table 4. For statistical analysis, we used the statistical programming language R [63] and used RStudio [64] to perform basic descriptive and regression analysis.…”
Section: ) Statistical Analysismentioning
confidence: 72%
“…Data mining techniques can analyze more valuable information hidden in a large number of datasets [9]. Educational data mining is to know and analyze the situation of students from educational data through learning analysis tools [10]. Therefore, we investigated the application of various data mining techniques and machine learning models in the field of education.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Costa et al used educational data mining (EDM) techniques to predict student failure rates in introductory programming courses at an early enough stage [12]. Abidi et al identified in advance the student group who would be confused when doing algebra homework by seven machine learning methods such as random forest (RF) and gradient boosting tree (XGBoost) to help them learn knowledge and develop talent [10]. Jokhan et al developed an early warning system (EWS) to predict student performance in an IT course at a university in the South Pacific area through the correlation between online behavior and grades, with a prediction accuracy of 60.8% [13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Uskov et al (2019) examined the machine learning predictions of student academic performance in STEM (Science, Technology, Engineering, and Mathematics) education. Abidi et al (2019) investigated models for predicting confused students who try to do homework using ITS (Intelligent tutoring systems). In their studies, they used naïve Bayes (NB), generalized linear model (GLM), logistic regression (LR), deep learning (DL), decision tree (DT), random forest (RF), and gradient boosted trees (XGBoost) machine learning models.…”
Section: Introductionmentioning
confidence: 99%